Uric acid and HDL-C-derived inflammatory ratios as biomarkers in schizophrenia and major depressive disorder: a retrospective study - Chen, Hao; Qiu, Min; Zhang, Haiqing; Huai, Yan; Huang, Qiuyan; Li, Ping; Lei, Yingjia; Jiang, Yufeng; Li, Qifeng; Zhang, Shaochuan (Frontiers in Psychiatry, 2025)
BackgroundRatios derived from uric acid (UA) and high-density lipoprotein cholesterol (HDL-C) represent novel composite indicators integrating metabolic and inflammatory information. These ratios include the uric acid-to-lymphocyte ratio (ULR), uric acid-to-HDL-C ratio (UHR), uric acid-to-creatinine ratio (UCR), uric acid-to-albumin ratio (UAR), neutrophil-to-HDL-C ratio (NHR), lymphocyte-to-HDL-C ratio (LHR), monocyte-to-HDL-C ratio (MHR), and platelet-to-HDL-C ratio (PHR). This retrospective study aimed to evaluate and compare the predictive ability of these indicators in distinguishing patients with schizophrenia (SCZ) or major depressive disorder (MDD) from healthy controls (HCs) to identify potential biomarkers.Materials and methodsBlood parameter data were collected from 442 patients with SCZ, 326 with MDD, and 222 healthy controls. A retrospective analysis was conducted to examine intergroup differences in the UA- and HDL-C-derived ratios. The predictive efficacy of these parameters was assessed using receiver operating characteristic (ROC) curve analysis.ResultsSignificant intergroup differences in biomarker levels were observed. The UHR, UAR, NHR, and MHR were identified as predictive factors for distinguishing the SCZ group from the HC group, while the UAR and MHR distinguished the MDD group from the HC group. A composite model of the UHR, UAR, NHR, and MHR in the SCZ group yielded an area under the curve (AUC) of 0.877 (p<0.001). Similarly, a composite model of the UAR, UCR, UHR, and MHR in the MDD group produced an AUC of 0.818 (p<0.001).ConclusionThis study indicated that the ratio derived from UA and HDL-C more comprehensively reflects the inflammatory and metabolic status, and its expression differences can significantly distinguish SCZ and MDD.